(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Aerated concrete blocks are made according to the design proportions in this project. Cement, fine particles, a foaming agent, and water are the ingredients of foam concrete. Sand prices are significantly rising these days. We may lower the cost of sand by replacing it with a replacement material. In the current investigation, sand is partially substituted by varying weights and quantities of blast furnace slag, fly ash, and glass powder. To gain a better understanding of the utilization of blast furnace slag, Fly Ash, and glass powder in various literatures, their impact on Compressive Strength foam concrete is explored.